PROTECTION OF MULTI INPUT MULTI OUTPUT MOBILE COMMUNICATION AGAINST MANMADE JAMMING AND INTERFERENCES - Jamal Mohammed Rasool; Noor Jamal Jihad (Journal of Engineering and Sustainable Development, 2019)
Recently, the use of mobile communications has become very popular but a huge problem of manmade and other kinds of interferences have been appeared and there are specific manners which many people used against this kind of communication although CDMA techniques has a good protection of these kinds of noise which don't mention it in this paper .Multiple Inputs Multiple outputs (MIMO) techniques has high capacity, increased diversity, and interference suppression. In this paper the model of receiver with MIMO techniques has introduced by using MATLAB 2014b to show the scan of the beam of antenna and measure the received power to get the best situation to make the call by suppression the signal from the direction which is many more the specific threshold.